Gathering a heritage : Ukrainian, Slavonic, and ethnic Canada and the USA - Prymak, Thomas M. (Thomas Michael), 1948- (University of Toronto Press, 2015)
Since the 1970s and 1980s, the study of immigration and ethnicity has grown to become an essential aspect of North American history. In Gathering a Heritage, Thomas M. Prymak uses the essays and articles he has written over the past thirty years as a historian of Ukrainian and Ukrainian Canadian history to reflect on the evolution of ethnic studies in Canada and the United States.The essays included in this book explore the history of Ukrainian and Slavonic immigration to North America and the literature through which these communities and their historians have sought to recapture their past. Each previously published essay is revised and expanded and several more appear here for the first time - including the fascinating story of French Canadian writer Gabrielle Roy's connections with Ukrainian Canadians and her tumultuous affair with a Ukrainian Canadian nationalist in pre-war London.